Implementasi Metode Certainty Factor Berbasis Android Pada Sistem Pakar Diagnosa Kecanduan Smartphone - Aries Muarriful Aziz; Yudo Bismo Utomo; Dian Efytra Yuliana (ZETROEM, 2022)
Storing human knowledge in certain fields into the system to analyze a problem so that the system can make intelligent decisions as experts do and solve the problem. The tendency of excessive and inappropriate use of smartphones can lead to addiction, the impact of which can interfere with social interaction with the surrounding community and damage eye health, many people do not realize that there are changes that occur when they are addicted to smartphones, so a system that is able to analyze and provide solutions is needed addiction to smartphones. This study designs an expert system that will be used to analyze smartphone addiction. Users of this application seem to be dealing directly with experts in the field of psychology. The system design is carried out by creating a knowledge base and converting it into various rules as a description of knowledge. The system is designed by implementing the certainty factor method and using the Android Studio application to design the appearance as well as to build this expert system application. The results of this study reveal the level of addiction to smartphones and the solutions for each level. Application testing is also carried out to determine the accuracy of the system. The results of this test can be concluded that the expert system is good enough even though it can only analyze 3 levels of addiction, and the accuracy of this expert system application is 86.67%.